Thanatophoric dysplasia type 1 (TD1): a case report - Sharma, Deepti; Sharma, Chandra Madhur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Thanatophoric Dysplasia (TD) is a severe short-limb dwarfism syndrome that is usually lethal in the perinatal period. It is characterized by shortening of the limbs, severely small thorax, large head with a prominent forehead, macrocephaly, curved femur, and flattened vertebral bodies. Thanatophoric dysplasia is divided into 2 clinically defined subtypes: thanatophoric dysplasia type 1 & type 2 (TD1 & TD2). We report this case because of its rarity with review of literature.